Ising-like behaviour of mesoscopic magnetic chains. (17th August 2018) - Östman, Erik; Arnalds, Unnar B; Kapaklis, Vassilios; Taroni, Andrea; Hjörvarsson, Björgvin
Abstract: We demonstrate an experimental realization of the short range magnetic order in a one-dimensional Ising chain using fabricated mesospins. We confirm an excellent agreement between the experimental findings and simulations obtained using the original Ising model. In particular, we are able to show that the thermal behaviour of the mesoscopic Ising chain dominates over the thermal behaviour of the individual mesospins themselves, confirming that fabricated mesospins can be viewed as artificial magnetic atoms.